“To Study the Quality of Life of Patients with Type 2 Diabetes Complicated by Polyneuropathy” (Texas Journal of Medical Science, 2022)
Diabetes mellitus (DM) is one of the most common metabolic diseases, and the number of cases has increased worldwide. According to the International Diabetes Federation (IDF), the number of patients with diabetes will increase from 387 million in 2014 to 592 million in 2035. With a global prevalence of 8.3%, DM represents a worldwide problem [1]. Diabetic neuropathies are the most prevalent chronic complications of diabetes. This heterogeneous group of conditions affects different parts of the nervous system and presents with diverse clinical manifestations. Chronic sensorimotor DPN is the most common form of DN.3-5 A major symptom in DN patients is pain arising as a direct consequence of abnormalities in the peripheral somatosensory system in people with diabetes. 4 The symptoms can be present as severe numbness, paresthesia, or hyperesthesia, however, DPN may be asymptomatic in about 50% of patients 5 and as the DPN progresses, the painful symptoms usually disappear although they have a substantial impact in quality of life (QoL).